Representation of Religious Tolerance in the Origin Story of Kelenteng Jamblang Cirebon - Widianti, Nurhannah; Nuryatin, Agus; Supriyanto, Teguh; Pristiwati , Rahayu (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Religious tolerance is a cornerstone of social harmony in Indonesia’s multicultural society, yet its consistent practice remains a challenge amid ongoing cases of religious discrimination and intolerance. While Indonesia is often praised globally for its interfaith harmony, there is still a significant gap between the ideal values of tolerance and their implementation in daily life. This study aims to examine how the values of religious tolerance are represented in the local folklore Kelenteng Jamblang from Cirebon, West Java, which narrates the harmonious interaction between Chinese and Muslim communities in the past. Using a descriptive qualitative approach with content analysis, the research analyzes narrative elements, character actions, and symbolic representations within the folklore text. The findings reveal that inclusive leadership, mutual respect across religious boundaries, and collective action such as gotong royong are core reflections of religious moderation within the story. The character of Njo Kie Tjit, who embodies dual cultural and religious identities, serves as a central figure showing that tolerance is practiced through concrete social actions. The conclusion highlights that traditional folklore can serve as a valuable medium for transmitting interfaith values, strengthening the spirit of pluralism and religious moderation. This study implies that incorporating local narratives into education and interfaith dialogue can reinforce inclusive values and contribute to social cohesion in contemporary multicultural societies.